Investigation of magnesium–zinc–calcium alloys and bone marrow derived mesenchymal stem cell response in direct culture. (15th January 2015) - Cipriano, Aaron F.; Sallee, Amy; Guan, Ren-Guo; Zhao, Zhan-Yong; Tayoba, Myla; Sanchez, Jorge; Liu, Huinan
Graphical abstract: Abstract: Crystalline Mg–Zn–Ca ternary alloys have recently attracted significant interest for biomedical implant applications due to their promising biocompatibility, bioactivity, biodegradability and mechanical properties. The objective of this study was to characterize as-cast Mg–xZn–0.5Ca (x = 0.5, 1.0, 2.0, 4.0 wt.%) alloys, and determine the adhesion and morphology of bone marrow derived mesenchymal stem cells (BMSCs) at the interface with the Mg–xZn–0.5Ca alloys. The direct culture method (i.e. seeding cells directly onto the surface of the sample) was established in this study to probe the highly dynamic cell–substrate interface and thus to elucidate the mechanisms of BMSC responses to dynamic alloy degradation. The results showed that the BMSC adhesion density on these alloys was similar to the cell-only positive control and the BMSC morphology appeared more anisotropic on the rapidly degrading alloy surfaces in comparison with the cell-only positive control. Importantly, neither culture media supplemented with up to 27.6 mM Mg 2+ ions nor media intentionally adjusted up to alkaline pH 9 induced any detectable adverse effects on BMSC responses. We speculated that degradation-induced dynamic surface topography played an important role in modulating cell morphology at the interface. This study presents a clinically relevant in vitro model for screening bioresorbable alloys, and provides useful design guidelines for determining the degradation rate of implants made of Mg–Zn–Ca alloys.